DINAMIKA PESANTREN DALAM LINGKARAN NAHDHOTUL ULAMA - Alfurqan, Alfurqan; Zuhdiyah, Zuhdiyah; In'ami, Moh (Universitas Islam Nahdlatul Ulama Jepara, 2022)
One of the strengths that NU has is in the form of cultural and ideological strength so that the nahdhiyyin (jama'ah) citizens are so eager to manage education to fight for the realization of NU's ideals. Although managerial, this is certainly not ideal. For this reason, Nahdhotul Ulama needs to strengthen its role as a regulator and facilitator for all education units within the NU, both Jam'iyah and jama'ah. NU pesantren must carry out various kinds of transformation, namely: first, curriculum reorientation. Second, contextualization of the yellow book. Third, Build a Library. Fourth, Promote Translation. Fifth, Publishing. Sixth, Conduct professional training. Seventh, mastery of technology.